The Influence of Licorice Root (Glycyrrhiza glabra) on Sex Reversal in Guppy Poecilia reticulata - Funda Turan (International Journal of Secondary Metabolite)
The roots and rhizomes of licorice (Glycyrrhiza) species have long been used worldwide as a herbal medicine and natural sweetener. Licorice is commonly present in menopausal botanical supplements in the United States. The estrogenic activities of different licorice species are variable and likely depend on the type and amounts of bioactive compounds. This study examined the effects of Licorice root extract on sex reversal in guppy, Poecilia reticulata. Newly born guppy fry (0.014 ± 0.001 mean weight), were randomly distributed into 30 L aquaria at a density of 80 fish per aquarium and subjected to a sex-reversal treatment by immersion application of licorise root extract for 30 days. The licorise root extract was incorporated into the aquarium water as follows: 0 (control), 0.25 and 0.5 g/ L licorice root extract. Each of the treatment group was randomly assigned to triplicate groups of fish. The treatment was repeated twice (in the beginning and half way through the experiment) during 30 days. At the end of experiment, the highest feminization (88%) was observed at 0.5 gŁ licorise root extract group. Morphological and histological examinations of the gonads in all groups revealed no intersex fish. Histological examination of fish treated with licorise root revealed no damage to the testes or ovaries. This study demonstrated successful sex reversal with treatment of licorise root on new-born progenies of P. reticulate.